Clinical manifestations and treatment outcomes in prurigo pigmentosa (Nagashima disease): A systematic review of the literatureCapsule Summary - Asfandyar Mufti, MD; Sara Mirali, PhD; Abrahim Abduelmula, BScN; Katherine Ann McDonald, MD; Shaikhah Alabdulrazzaq, BMBCh; Muskaan Sachdeva, BHSc; Jensen Yeung, MD, FRCPC (Elsevier, 2021)
Background: Prurigo pigmentosa (PP) is a rare inflammatory dermatosis characterized by pruritic erythematous papules that coalesce to form a reticulate pattern. PP is often misdiagnosed, and patients are treated with ineffective therapies. Although the majority of reports about PP are from East Asia, patients of all backgrounds can be affected. Objectives: To perform a systematic review of reported PP cases with the purpose of summarizing the clinical presentation and treatment of PP. Methods: MEDLINE and Embase were searched for original articles describing PP. We identified 115 studies from 24 countries representing 369 patients to include in the analysis. Results: Of the 369 patients included in the analysis, the mean age was 25.6 years (range: 13-72 years) with 72.1% (266 of 369) female. Risk factors or aggravating factors were described in 52.3% (193 of 369) of patients and included dietary changes (25.5%, 94 of 369), friction (8.4%, 31 of 369), sweat (7.6%, 28 of 369), and ketonuria (5.1%, 19 of 369). Of those patients who experienced PP following dietary changes, 40.4% (38 of 94) started a ketogenic diet. Minocycline monotherapy was the most frequently prescribed treatment for PP (20.9%, 77 of 369), achieving complete resolution in 48.1% (37 of 77) of patients. Conclusions: PP is sometimes associated with ketogenic diets and can be effectively managed with oral tetracyclines.